Variational Approach to Impulsive Problems: A Survey of Recent Results - Fang-fang Liao; Juntao Sun (Abstract and Applied Analysis)
We present a survey on the existence of nontrivial solutions to impulsive differential equations by using variational methods, including solutions to boundary value problems, periodic solutions, and homoclinic solutions.